2020
DOI: 10.3389/fonc.2020.532924
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nomogram to Predict Lymph Node Metastasis in Patients With T1 High-Grade Urothelial Carcinoma of the Bladder

Abstract: Purpose This study aims to develop and validate a nomogram to predict lymph node (LN) metastasis preoperatively in patients with T1 high-grade urothelial carcinoma. Methods We retrospectively evaluated the data of 2,689 patients with urothelial carcinoma of the bladder (UCB) treated with radical cystectomy (RC) and bilateral lymphadenectomy in two medical centers. Eventually, 412 patients with T1 high-grade urothelial carcinoma were enrolled in the primary cohort to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…First, the largest diameter of the primary bladder tumor was a selected predictor, and patients with primary tumor larger than 49-57 mm had higher risk of pelvic LN involvement. This is in line with previously published studies that reported the primary bladder tumor size to be associated with the risk of LN involvement [19] and distant metastases [20]. Of note, the largest diameter of primary tumor was measured when visible on PET and/or non-contrast enhanced CT from [ 18 F]-FDG PET/CT performed after TURBT.…”
Section: Discussionsupporting
confidence: 90%
“…First, the largest diameter of the primary bladder tumor was a selected predictor, and patients with primary tumor larger than 49-57 mm had higher risk of pelvic LN involvement. This is in line with previously published studies that reported the primary bladder tumor size to be associated with the risk of LN involvement [19] and distant metastases [20]. Of note, the largest diameter of primary tumor was measured when visible on PET and/or non-contrast enhanced CT from [ 18 F]-FDG PET/CT performed after TURBT.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we used preoperative laboratory measurements and inflammatory biomarkers, including NLR, PLR, MLR, NPR, and SII, to predict LNM in BUC. Two previously published studies identified MLR, fibrinogen, and NLR as preoperative predictors of LNM in BUC and included them in nomograms (Ou et al 2020 ; Schuettfort et al 2022 ). Although most laboratory measurements (including MLR, fibrinogen, and NLR) included in our study were significantly different between BUC patients with LNM and those without in the univariate analysis, serum creatine was the only variable capable of independently predicting LNM in BUC before RC in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting models of tumor LNM have been established in thyroid papillary carcinoma, bladder urothelial carcinoma and early esophageal squamous cell carcinoma ( 14 – 16 ). To our knowledge, there are no predicting models for LNM in ES.…”
Section: Introductionmentioning
confidence: 99%